The music of Julián Bautista during his exile in Argentina. Confluences in Hispanic American modernity - Ogas, Julio (Revista Musical Chilena, 2019)
Julian Bautista settles in Argentina after Francisco Franco claimed power in Spain. His concert production at this stage is not extensive, however the themes he addresses and the stylistic characteristics of the works of this period show his process of adaptation to the musical environment that welcomes him. In this paper, first, an analysis of the development of his compositional style is made in this period and, later, some connections of this material are established with the cultural and musical framework of Buenos Aires.